Pole piece, preparation method thereof and battery
By setting laser-etched recesses on the electrode and covering them with a protective layer, the problems of short circuits and self-discharge caused by dust in lithium-ion batteries are solved, the electrolyte penetration capacity and lithium-ion migration speed are improved, and the rate performance of the battery is enhanced.
Patent Information
- Application Number
- CN202411411800.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-07
AI Technical Summary
In lithium-ion batteries, increased electrode thickness leads to poor electrolyte penetration, making lithium-ion migration difficult and affecting rate performance. At the same time, micron-sized dust generated by laser etching can easily cause internal short circuits or self-discharge in the battery.
Laser-etched recesses are formed on the active material layer of the electrode and covered with a protective layer containing an adhesive and a conductive agent. This protective layer covers dust and traps other dust particles, forming a bonding interface layer to reduce dust detachment.
It effectively prevents dust from entering the electrolyte, reduces the risk of internal short circuits and self-discharge in the battery, improves the electrolyte's permeability, alleviates concentration polarization, increases lithium-ion migration speed, and enhances the battery's rate performance.
Smart Images

Figure CN119275233A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery manufacturing, and in particular to a pole piece, a method for preparing a pole piece, and a battery. Background Art
[0002] With the rapid development of the new energy vehicle industry, the requirements for the energy density of lithium-ion batteries are getting higher and higher. The ideal way to improve the energy density of lithium-ion batteries is to increase the thickness of the pole piece to increase the content of active substances. However, in lithium-ion batteries, the thicker the pole piece, the worse the penetration of the electrolyte, which increases the concentration polarization inside the pole piece during the charge and discharge process of the lithium-ion battery, making lithium ion migration difficult, which will limit the rate performance of the lithium-ion battery to a certain extent.
[0003] In order to improve the effect of electrode infiltration into electrolyte, the related technology uses laser etching to etch grooves or holes on the active material layer of the electrode, so that the electrolyte can quickly penetrate into the interior of the active material layer through the grooves or holes. However, when laser etching grooves or holes is used, it is easy to cause micron-level dust to remain on the surface of the active material layer (especially the inner surface of the grooves or holes), that is, there is a problem of floating powder. These micron-level dusts mainly come from loose active materials and conductive agents and carbonized binders, which are difficult to remove by dust removal equipment. Therefore, when the electrode is used to prepare a battery, these dusts are easily brought into the battery's diaphragm through the electrolyte, causing internal short circuits or increased self-discharge of the battery. Summary of the invention
[0004] The embodiments of the present application provide a pole piece, a method for preparing a pole piece, and a battery, which can improve the technical problem of powder floating on the surface of the pole piece.
[0005] In a first aspect, an embodiment of the present application provides a pole piece, comprising:
[0006] current collector;
[0007] an active material layer, located on the current collector, the active material layer having a first surface facing away from the current collector, and a laser-etched concave portion extending from the first surface to the interior of the active material layer;
[0008] A protective layer covers the first surface and the inner surface of the laser-etched concave portion, and the protective layer includes a first adhesive.
[0009] In one embodiment, the protective layer adapts to the laser-etched recess and defines a receiving groove, and the notch of the receiving groove is located on a side of the protective layer away from the active material layer.
[0010] In one embodiment, the protection layer further includes a second active material.
[0011] In one embodiment, the protection layer further includes a first conductive agent.
[0012] In one embodiment, the ability of the protection layer to absorb the electrolyte is better than the ability of the active material layer to absorb the electrolyte.
[0013] In one embodiment, the porosity of the protection layer is greater than the porosity of the active material layer.
[0014] In one embodiment, the active material layer includes a first active material, and the oil absorption value of the first conductive agent is greater than the oil absorption value of the first active material.
[0015] In one embodiment, the active material layer further includes a second conductive agent, and the mass content of the first conductive agent in the protective layer is greater than the mass content of the second conductive agent in the active material layer.
[0016] In one embodiment, the active material layer includes a first active material, the content of the first active material in the active material layer is greater than 50 wt %, and the total mass percentage of the first conductive agent in the protective layer is greater than 50 wt %.
[0017] In one embodiment, the protective layer includes 1 wt % to 80 wt % of the first conductive agent, 10 wt % to 99 wt % of the first binder, and the protective layer further includes 0 wt % to 30 wt % of a dispersant.
[0018] In one embodiment, the protective layer includes 58 wt % to 75 wt % of the first conductive agent, 12.5 wt % to 30 wt % of the first binder, and 8 wt % to 12.5 wt % of the dispersant.
[0019] In one embodiment, the dispersant includes at least one of anhydride, polyvinyl pyrrolidone, sulfate, poly(N-vinyl acetamide), polyvinyl alcohol, sulfonate and polyethylene glycol; or, the dispersant includes at least one of ionic dispersant, non-ionic dispersant and polymer dispersant.
[0020] In one embodiment, the first conductive agent includes at least one of a conductive carbon material and a conductive ceramic.
[0021] In one embodiment, the conductive carbon material includes at least one of carbon black, carbon nanotubes, carbon fibers, acetylene black, graphite and graphene.
[0022] In one embodiment, the specific surface area of the first conductive agent is 1 m 2 / g~1000m 2 / g; and / or, the D50 particle size of the first conductive agent is 1nm~50μm; and / or, the oil absorption value of the first conductive agent is greater than or equal to 500mL / 100g; and / or, the conductivity of the first conductive agent is 3000S·cm~12000S·cm.
[0023] In one embodiment, the first binder includes at least one of carboxymethyl cellulose, polyacrylic acid, polyvinylidene fluoride, polytetrafluoroethylene and styrene-butadiene rubber.
[0024] In one embodiment, the laser-etched recess includes at least one of a groove and a through hole.
[0025] In one embodiment, the laser-etched concave portion comprises an elongated groove extending along a first direction of the active material layer, and a length of the groove extending in the first direction is less than or equal to a length of the active material layer in the first direction.
[0026] In one embodiment, along a direction approaching the current collector, the width of the laser-etched recess remains unchanged or becomes smaller.
[0027] In one embodiment, the sidewalls of the laser-etched recess are straight or curved, or, when cut along the thickness direction of the active material layer, the cross-section of the laser-etched recess is V-shaped, trapezoidal, square, semicircular or elliptical.
[0028] In one embodiment, the number of the laser-etched recesses is multiple, the multiple laser-etched recesses are distributed at intervals, and the spacing between two adjacent laser-etched recesses is 0.01 mm to 100 mm; and / or the depth of the laser-etched recess is less than or equal to the thickness of the active material layer; and / or the average width of the laser-etched recess is 1 μm to 300 μm.
[0029] In one embodiment, the thickness of the protective layer is 0.2 μm to 50 μm; or, the thickness of the protective layer is 0.2 μm to 10 μm; or, the porosity of the protective layer is 5% to 99%.
[0030] In one embodiment, the thickness of the active material layer is greater than 30 μm; or the thickness of the pole piece is greater than 60 μm.
[0031] In a second aspect, an embodiment of the present application further provides a method for preparing a pole piece, comprising:
[0032] Disposing an active material layer on the current collector, the active material layer having a first surface facing away from the current collector;
[0033] Laser etching the active material layer to generate a laser-etched recess extending from the first surface into the active material layer;
[0034] Providing a first slurry, wherein the first slurry includes a first binder and a first solvent;
[0035] Performing a film-forming process on the first surface and the laser-etched concave portion with the first slurry to obtain a first wet film layer;
[0036] The first wet film layer is dried to evaporate the first solvent, thereby obtaining a protective layer.
[0037] In one embodiment, the first slurry further includes a first conductive agent and / or a second active material; and / or, the content of the first solvent in the first slurry is 10wt% to 97wt%; and / or, the solid content in the first slurry is 3wt% to 90wt%; and / or, the viscosity of the first slurry is 10cp to 15000cp; and / or, the first solvent includes at least one of water, N-methylpyrrolidone, ethylene glycol and isopropanol.
[0038] In one embodiment, providing an active material layer on the current collector includes:
[0039] providing a second slurry, the second slurry comprising a first active material, a second binder, and a second solvent;
[0040] Performing a film-forming process on the second slurry on the current collector to obtain a second wet film layer;
[0041] The second wet film layer is dried to evaporate the second solvent, thereby obtaining an active material layer.
[0042] In a third aspect, an embodiment of the present application further provides a battery, comprising a pole piece as described in the first aspect of the embodiment of the present application or a pole piece prepared by the method for preparing the pole piece as described in the second aspect of the embodiment of the present application.
[0043] Beneficial effects of the embodiments of the present application:
[0044] In an embodiment of the present application, a pole piece includes a current collector and an active material layer arranged on the current collector, and a laser-etched recess prepared by a laser etching process is opened on the active material layer. Furthermore, the pole piece also includes a protective layer, which covers the first surface of the active material layer and the inner surface of the laser-etched recess. The protective layer can cover the dust remaining on the surface of the active material layer to prevent the dust from entering the electrolyte, and the first binder contained in the protective layer can also stick to the dust, especially at the inner surface of the laser-etched recess. The first binder will penetrate into the active material layer in small amounts to form a bonding interface layer between the protective layer and the active material layer. Not only will a large amount of residual dust be solidified in the bonding interface layer, but the bonding interface layer can also prevent the loose material on the side wall of the laser-etched recess from further loosening, thereby ultimately reducing the dust from detaching from the pole piece and reducing the risk of internal short circuit or self-discharge of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0046] Figure 1 is a schematic cross-sectional structural diagram of a first pole piece provided in an embodiment of the present application;
[0047] Figure 2 yes Figure 1 A schematic diagram of the cross-sectional structure of the active material layer;
[0048] Figure 3 yes Figure 1 Schematic diagram of the cross-sectional structure of the middle protective layer;
[0049] Figure 4 is a schematic cross-sectional structural diagram of a second pole piece provided in an embodiment of the present application;
[0050] Figure 5 is a schematic cross-sectional structural diagram of a third type of pole piece provided in an embodiment of the present application;
[0051] Figure 6 is a schematic cross-sectional structural diagram of a fourth pole piece provided in an embodiment of the present application;
[0052] Figure 7 is a schematic diagram of a top view of the structure of an active material layer in a fifth pole piece provided in an embodiment of the present application;
[0053] Figure 8 is a flow chart of the preparation of the pole piece provided in the embodiment of the present application;
[0054] Fig. 9 It is a schematic diagram of the structure of a battery provided in an embodiment of the present application.
[0055] Fig.10 is a SEM image of the electrode provided in Example 8, in which A refers to the active material layer and B refers to the conductive layer;
[0056] Fig.11 yes Fig.10 Enlarged SEM image of the framed part;
[0057] Fig.12 is a SEM image of the electrode provided in Example 1, in which A refers to the active material layer and B refers to the conductive layer;
[0058] Fig.13 yes Fig.12 Enlarged SEM image of the framed part;
[0059] Fig.14 is a SEM image of the pole piece provided in Comparative Example 1;
[0060] Fig.15 The following are photos of the surface cleanliness test of the electrode samples at different preparation stages provided in Example 8, wherein: Fig.15 (a) shows a sample surface cleanliness test photograph before laser etching of the active material layer; Fig.15 (b) shows a photo of the surface cleanliness test of the sample after laser etching of the active material layer; Fig.15 Figure (c) shows a photo of the surface cleanliness test of the sample after coating the conductive layer;
[0061] Fig.16 (a) is a photo of the electrode and the diaphragm provided in Example 1 after the electrode and the diaphragm are wound and then separated; Fig.16 Figure (b) shows a photograph of the electrode sheet and the diaphragm provided in Example 8 after the electrode sheet and the diaphragm are wound and then separated; Fig.16 Figure (c) shows a comparison of two diaphragms. The upper diaphragm in the figure is the diaphragm wound around the pole piece provided in Comparative Example 1, and the lower diaphragm in the figure is the diaphragm wound around the pole piece provided in Example 8.
[0062] Reference numerals:
[0063] 10. Pole piece;
[0064] 1. Current collector;
[0065] 2. active material layer; 21. first surface; 22. laser etched concave portion; 2a. second wet film layer;
[0066] 3. Protective layer; 3a. First wet film layer; 31. Receiving tank;
[0067] 100.Battery. DETAILED DESCRIPTION
[0068] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of this application.
[0069] In addition, it should be understood that the specific embodiments described herein are only used to illustrate and explain the present application, and are not used to limit the present application. In the present application, unless otherwise stated, the directional words used, such as "upper" and "lower", generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device.
[0070] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0071] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or mutual communication; it can be a direct connection, or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0072] The terms "comprises," "includes," or any other variation thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements, but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus. In the absence of further limitations, an element defined by the phrase "comprises a ..." does not exclude the presence of additional identical elements in the process, method, article, or apparatus that includes the element.
[0073] In the description of the embodiments of the present application, words such as "example" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "example" or "for example" in the embodiments of the present application is not to be interpreted as being more preferred or having more advantages than another embodiment or design. The use of words such as "example" or "for example" is intended to present relative concepts in a clear manner.
[0074] To facilitate understanding of the scheme of the present application, the spline curves and arrows used in the drawings are explained here: the components indicated by the spline curves without arrows are solid components, that is, components with solid structures; the components indicated by the spline curves with arrows are virtual components, that is, components without solid structures.
[0075] The embodiments of the present application provide a pole piece, a method for preparing a pole piece, and a battery, and the embodiments are described in detail below.
[0076] First, see Figures 1 to 7 An embodiment of the present application provides a pole piece 10 , which includes a current collector 1 , an active material layer 2 and a protective layer 3 .
[0077] The active material layer 2 is located on the current collector 1 and has a first surface 21 facing away from the current collector 1. A laser-etched concave portion 22 is also formed on the active material layer 2 and extends from the first surface 21 to the inside of the active material layer 2.
[0078] The protective layer 3 covers the first surface 21 of the active material layer 2 and the inner surface of the laser-etched concave portion 22. The protective layer 3 includes a first binder, that is, the protective layer 3 is a layer structure including at least the first binder.
[0079] The electrode sheet 10 can be applied to a battery 100, such as a secondary battery, including but not limited to a lithium-ion battery. The electrode sheet 10 can be a positive electrode sheet or a negative electrode sheet. When the electrode sheet 10 is a positive electrode sheet, the current collector 1 is a positive electrode current collector, and the active material layer 2 is a positive electrode active material layer; when the electrode sheet 10 is a negative electrode sheet, the current collector 1 is a negative electrode current collector, and the active material layer 2 is a negative electrode active material layer.
[0080] If the current collector 1 is a positive electrode current collector, as an example, the current collector 1 can be aluminum foil, carbon-coated aluminum foil, safety-primed aluminum foil, etched aluminum foil or aluminum mesh. The thickness of the current collector 1 can be 5 μm to 20 μm, for example 5 μm, 10 μm, 15 μm or 20 μm.
[0081] If the current collector 1 is a negative electrode current collector, as an example, the current collector 1 can be a copper foil having a thickness of 3 μm to 20 μm, for example, 3 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm or 20 μm.
[0082] The current collector 1 has two side surfaces opposite to each other along the thickness direction of the current collector 1 . The active material layer 2 is arranged on the current collector 1 . The active material layer 2 may be combined with one side surface of the current collector 1 or with both side surfaces of the current collector 1 .
[0083] The active material layer 2 is a layer structure including at least an active material. Optionally, the active material layer 2 includes at least a first active material and a second binder. In other words, the active material layer 2 is a mixed layer including at least a first active material and a second binder. When the types of the active material layer 2 are different, the selection of the first active material and the second binder contained therein will also be different. Optionally, the active material layer 2 also includes a second conductive agent. Of course, in some embodiments, the active material layer 2 may not include a conductive agent, that is, a conductive agent-free formula design. The following is an example in which the active material layer 2 includes a first active material, a second binder, and a second conductive agent.
[0084] If the active material layer 2 is a positive electrode active material layer, the first active material is a positive electrode active material. As an example, the first active material includes at least one of nickel cobalt manganese ternary material (NMC), lithium cobalt oxide (LiCoO2), lithium iron phosphate (LiFePO4, LFP), lithium manganese oxide (LiMn2O4, LMO) and nickel cobalt aluminum oxide (NCA). Similarly, the second conductive agent is a positive electrode conductive agent. As an example, the second conductive agent includes at least one of carbon black, conductive graphite, graphene and carbon nanotubes. Similarly, the second binder is a positive electrode binder, and the second binder includes at least one of organic polymers such as polyacrylic acid (PAA) and polyvinylidene fluoride (PVDF).
[0085] If the active material layer 2 is a negative electrode active material layer, the first active material is a negative electrode active material, and as an example, the first active material includes at least one of graphite, graphene, hard carbon, soft carbon and silicon-based materials. Similarly, the second conductive agent is a negative electrode conductive agent, and as an example, the second conductive agent includes at least one of carbon black, graphene, acetylene black, carbon nanotubes and conductive graphite. Similarly, the second binder is a negative electrode binder, and as an example, the second binder includes styrene butadiene rubber (SBR).
[0086] For the sake of distinction, the surface of the active material layer 2 facing away from the current collector 1 is referred to as the first surface 21. The side of the active material layer 2 away from the current collector 1 is concave-convex. Specifically, a laser-etched concave portion 22 is provided on the active material layer 2, and the laser-etched concave portion 22 extends from the first surface 21 to the inside of the active material layer 2, and the opening of the laser-etched concave portion 22 is located on the first surface 21 (that is, the opening faces outward). As an example, the laser-etched concave portion 22 may extend along the thickness direction of the active material layer 2, and the depth of the laser-etched concave portion 22 is less than or equal to the thickness of the active material layer 2. Usually, there are some undepressed positions on the active material layer 2, and this part is formed as a convexity, so that the side of the active material layer 2 away from the current collector 1 presents a concave-convex structure.
[0087] Laser etching the concave portion 22 refers to using a high energy density laser beam to locally irradiate the active material layer 2, so that the material in the local area of the active material layer 2 is vaporized and evaporated in a very short time to obtain a concave structure. As an example, the laser etched concave portion 22 includes at least one of a groove and a through hole. Optionally, the groove includes a blind hole. The laser etched concave portion 22 is prepared by laser etching, which is not only efficient, but also easy to control the shape and size of the laser etched concave portion 22. The number of laser etched concave portions 22 on the active material layer 2 can be one or more.
[0088] The active material layer 2 covers the first surface 21, that is, the protective layer 3 is located on the side of the active material layer 2 away from the current collector 1. It can be understood that the active material layer 2 and the protective layer 3 are sequentially distributed in the direction away from the current collector 1, the active material layer 2 is located between the current collector 1 and the protective layer 3, and the active material layer 2 is closer to the current collector 1 than the protective layer 3.
[0089] The protective layer 3 also covers the inner surface of the laser-etched recess 22. It can be understood that the protective layer 3 also extends into the laser-etched recess 22 and covers the inner wall surface of the laser-etched recess 22, which includes the bottom wall surface and the side wall surface.
[0090] The protective layer 3 includes a first binder, that is, the first binder can enable the protective layer 3 and the active material layer 2 to be combined together. Here, the first binder and the second binder can be the same or different. As an example, the first binder includes at least one of organic polymer materials such as carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE) and styrene-butadiene rubber (SBR).
[0091] In the embodiment of the present application, the pole piece 10 includes a current collector 1 and an active material layer 2 arranged on the current collector 1, and a laser-etched recess 22 prepared by a laser etching process is opened on the active material layer 2. Furthermore, the pole piece 10 also includes a protective layer 3, and the protective layer 3 covers the first surface 21 of the active material layer 2 and the inner surface of the laser-etched recess 22. The protective layer 3 can cover the dust remaining on the surface of the active material layer 2 to prevent the dust from entering the electrolyte, and the first binder contained in the protective layer 3 can also stick to the dust, especially at the inner surface of the laser-etched recess 22. The first binder will penetrate into the active material layer 2 in small amounts to form a bonding interface layer (not shown) between the protective layer 3 and the active material layer 2. Not only will a large amount of residual dust be solidified in the bonding interface layer, but the bonding interface layer can also prevent the loose material on the side wall of the laser-etched recess 22 from further loosening, thereby ultimately reducing the dust from detaching from the pole piece 10 and reducing the risk of internal short circuit or self-discharge of the battery 100.
[0092] In some embodiments, the protective layer 3 further includes a first conductive agent. The first conductive agent can make the protective layer 3 have a certain conductivity, which not only facilitates the transmission of current between the protective layer 3 and the active material layer 2, but also reduces the internal resistance of the pole piece 10. Generally, the conductive agent has a strong ability to absorb electrolyte. Adding the first conductive agent to the protective layer 3 can also enhance the ability of the protective layer 3 to infiltrate the electrolyte. The first conductive agent and the second conductive agent may be the same or different. As an example, the first conductive agent includes at least one of a conductive carbon material and a conductive ceramic. Optionally, the conductive carbon material includes at least one of carbon black, carbon nanotubes, carbon fibers, acetylene black, graphite and graphene. Optionally, the carbon black includes at least one of conductive carbon black Super P, superconducting carbon black and Ketjen black. Optionally, the carbon nanotubes include at least one of single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs). Optionally, the conductive ceramic includes at least one of CaF2 structured substances such as β-Al2O3, CaO·ZrO2 and Y2O3·ZrO2. In the protective layer 3 , a first binder and a first conductive agent are mixed together.
[0093] In some embodiments, see Figures 1 to 3 , Figure 6 , the protective layer 3 adapts to the laser-etched concave portion 22 and defines a receiving groove 31, the notch of which is located on the side of the protective layer 3 away from the active material layer 2. That is, the protective layer 3 extends into the laser-etched concave portion 22 but does not fill the laser-etched concave portion 22, the protective layer 3 adapts to the inner side wall of the laser-etched concave portion 22 and bends and extends, and a receiving groove 31 is formed in the corresponding bending area of the protective layer 3, and the receiving groove 31 corresponds to the laser-etched concave portion 22 and is located in the laser-etched concave portion 22. In this case, the protective layer 3 is usually thin or the laser-etched concave portion 22 is relatively wide.
[0094] By providing the receiving groove 31, the distance between the protective layer 3 and the current collector 1 is shortened, and the opening of the receiving groove 31 faces the side away from the current collector 1, so that when the electrode 10 is applied to the battery 100, the electrolyte can quickly penetrate into the interior of the active material layer 2 through the receiving groove 31, thereby alleviating the concentration polarization inside the electrode 10.
[0095] In some embodiments, see Figure 1 , the number of laser-etched recesses 22 is multiple, and the multiple laser-etched recesses 22 are distributed at intervals on the active material layer 2, and the receiving grooves 31 are arranged one-to-one with the laser-etched recesses 22. In other words, the number of receiving grooves 31 is equal to the number of laser-etched recesses 22, which is also multiple. Optionally, the multiple laser-etched recesses 22 are distributed at equal intervals on the active material layer 2. By providing multiple laser-etched recesses 22 and receiving grooves 31, the uniformity of the active material layer 2 infiltrating the electrolyte can be improved.
[0096] In some embodiments, when the protective layer 3 is defined with a receiving groove 31, the protective layer 3 may further include a second active material. That is, the protective layer 3 includes at least a first binder and a second active material. By adding the second active material to the protective layer 3, the energy density of the pole piece 10 is improved. Here, the second active material may be the same as or different from the first active material. Optionally, the protective layer 3 also includes a first conductive agent.
[0097] It should be noted here that the selection of the second active material is related to the type of the electrode 10. When the electrode 10 is a positive electrode, the second active material is a positive electrode active material; when the electrode 10 is a negative electrode, the second active material is a negative electrode active material.
[0098] If the second active material is a positive electrode active material, as an example, the second active material includes at least one of nickel cobalt manganese ternary material (NMC), lithium cobalt oxide (LiCoO2), lithium iron phosphate (LiFePO4, LFP), lithium manganese oxide (LiMn2O4, LMO) and nickel cobalt aluminum oxide (NCA). If the second active material is a negative electrode active material, as an example, the second active material includes at least one of graphite, graphene, hard carbon, soft carbon and silicon-based materials.
[0099] In the case where the protective layer 3 is defined with the receiving groove 31, the receiving groove 31 can be used to promote the electrolyte to infiltrate the active material layer 2, so the ability of the protective layer 3 to absorb the electrolyte (abbreviated as liquid absorption) can be better than the ability of the active material layer 2 to absorb the electrolyte, or it can be weaker than the ability of the active material layer 2 to absorb the electrolyte. As an example, the protective layer 3 can be a conductive layer, that is, the protective layer 3 includes a first conductive agent and a first binder, but does not include an active material; the protective layer 3 can also be an active material layer, that is, the protective layer 3 also includes an active material, for example, the composition of the protective layer 3 can be the same as that of the active material layer 2.
[0100] In addition to providing the receiving groove 31, the rate at which the electrolyte infiltrates the active material layer 2 can also be increased by increasing the liquid absorption capacity of the protective layer 3. Here, the amount of electrolyte absorbed by a unit volume of material per unit time can be used to indicate the ability of the material to absorb electrolyte; generally, the larger the amount of electrolyte, the better the ability of the material to absorb electrolyte. The time taken by a unit volume of material to absorb a unit volume of electrolyte can also be used to indicate the ability of the material to absorb electrolyte; generally, the shorter the time, the better the ability of the material to absorb electrolyte. For example, the electrolyte absorption capacity of the protective layer 3 and the active material layer 2 can be tested by contact angle testing. Generally, the time for the same volume of electrolyte to completely enter the protective layer 3 is shorter than the time for it to completely enter the active material layer 2.
[0101] In some embodiments, compared to the active material layer 2, the protective layer 3 is a liquid absorbing layer, that is, the ability of the protective layer 3 to absorb electrolyte is better than that of the active material layer 2. In other words, compared to the active material layer 2, the electrolyte is more likely to infiltrate the protective layer 3. In combination with the protective layer 3 extending into the laser-etched recess 22, the electrolyte can preferentially enter the active material layer 2 through the portion of the protective layer 3 located in the laser-etched recess 22, shortening the path for the electrolyte to enter the interior of the active material layer 2, increasing the speed at which the active material layer 2 infiltrates the electrolyte, and alleviating the concentration polarization inside the pole piece 10. In this case, the protective layer 3 extends into the laser-etched recess 22, and the protective layer 3 may fill the laser-etched recess 22 or may not fill the laser-etched recess 22. Optionally, a receiving groove 31 is defined on the protective layer 3, and the receiving groove 31 is combined with the protective layer 3 to further increase the speed at which the active material layer 2 infiltrates the electrolyte.
[0102] In addition, by increasing the liquid absorption capacity of the protective layer 3, the protective layer 3 can also serve as an electrolyte carrier to store electrolyte, so that during the charging and discharging process of the electrode 10, the electrolyte stored in the protective layer 3 can be quickly supplied to the active material layer 2, especially the electrolyte stored in the portion of the protective layer 3 located on the inner surface of the laser-etched recess 22 can quickly enter the active material layer 2, promote the transmission of lithium ions in the electrode 10 and increase the migration speed of lithium ions, thereby reducing the concentration polarization inside the electrode 10.
[0103] In some embodiments, the porosity of the protective layer 3 is greater than the porosity of the active material layer 2. By increasing the porosity of the protective layer 3, the ability of the protective layer 3 to absorb the electrolyte can be improved, that is, the resistance of the electrolyte to flow in the protective layer 3 is less than the resistance to flow in the active material layer 2. Of course, the way to adjust the porosity of the protective layer 3 includes but is not limited to selecting a material with a lower compaction density, increasing the particle size of the material, reducing the compaction density of the protective layer 3, etc. For example, when preparing the active material layer 2, the active material layer 2 is first subjected to a roller pressing treatment, and when preparing the protective layer 3, no roller pressing treatment is performed. In this case, the protective layer 3 may contain a second active material or may not contain a second active material. Optionally, the protective layer 3 contains a second active material, and the average particle size of the second active material is greater than the average particle size of the first active material.
[0104] In some embodiments, the active material layer 2 includes a first active material, and the oil absorption value of the first conductive agent is greater than the oil absorption value of the first active material. Since the electrolyte mainly includes electrolytes and organic solvents, the ability of the protective layer 3 to absorb the electrolyte can be improved by increasing the oil absorption value of the first conductive agent in the protective layer 3, that is, the electrolyte is more easily absorbed by the protective layer 3 than the active material layer 2. Optionally, the protective layer 3 does not contain a second active material or contains a small amount of the second active material.
[0105] In some embodiments, the active material layer 2 further includes a second conductive agent, and the mass content of the first conductive agent in the protective layer 3 is greater than the mass content of the second conductive agent in the active material layer 2, that is, the content of the conductive agent in the protective layer 3 is higher than the content of the conductive agent in the active material layer 2. Generally, the conductive agent has a better ability to absorb electrolyte, and by increasing the mass content of the conductive agent (referred to as the first conductive agent) in the protective layer 3, the liquid absorption capacity of the protective layer 3 can be improved. Optionally, the protective layer 3 does not contain the second active material or contains a small amount of the second active material.
[0106] In some embodiments, the active material layer 2 includes a first active material, the content of the first active material in the active material layer 2 is greater than 50wt%, and the content of the first conductive agent in the protective layer 3 is greater than 50wt%. It can be understood that the active material layer 2 does not contain a second conductive agent or the content of the second conductive agent in the active material layer 2 is less than 50wt%, that is, the mass content of the first conductive agent in the protective layer 3 is greater than the mass content of the second conductive agent in the active material layer 2, thereby improving the liquid absorption capacity of the protective layer 3. As an example, the content of the first active material in the active material layer 2 is 50wt%, 60wt%, 70wt%, 80wt%, 85wt%, 90wt%, 92wt%, 94wt%, 95wt%, 96wt%, 97wt% or 98wt%. As an example, the content of the first conductive agent in the protective layer 3 is 50wt%, 60wt%, 70wt%, 80wt%, 85wt%, 90wt%, 92wt%, 94wt%, 95wt%, 96wt%, 97wt%, 98wt% or 99wt%.
[0107] In some embodiments, the protective layer 3 includes 1 wt% to 80 wt% of the first conductive agent, 10 wt% to 99 wt% of the first binder, and the protective layer 3 also includes 0 wt% to 30 wt% of the dispersant. That is, the protective layer 3 is a conductive layer, that is, the protective layer 3 does not contain active materials, and the protective layer 3 mainly includes conductive agents and binders, for example, the protective layer 3 only includes the first conductive agent and the first binder, or the protective layer 3 only includes the first conductive agent, the first binder and the dispersant. In the case where the protective layer 3 is a conductive layer, compared with the active material layer 2 containing the first active material and the second binder, the protective layer 3 can better absorb the electrolyte; in addition, the stability of the combination of the protective layer 3 and the active material layer 2 is improved, especially the first binder can better penetrate into the active material layer 2 from the inner wall surface of the laser-etched concave portion 22, and better solidify the inner wall of the laser-etched concave portion 22, thereby reducing the floating powder of the pole piece 10. As an example, in the protective layer 3, the content of the first conductive agent is 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt% or 80wt%; the content of the first binder is 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, 90wt% or 99wt%; the content of the dispersant is 0wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt% or 30wt%. When the protective layer 3 also includes a dispersant, the dispersant can effectively promote the dispersion of the first conductive agent in the first binder, especially when the first conductive agent is a conductive carbon material. Optionally, the dispersant is at least one of an ionic dispersant, a nonionic dispersant and a polymer dispersant. As an example, the dispersant includes at least one of anhydride, polyvinyl pyrrolidone (PVP), sulfate, sulfonate, poly (N-vinyl acetamide) (PNVA), polyvinyl alcohol (PVA) and polyethylene glycol. In the protective layer 3, the first binder, the first conductive agent and the dispersant are mixed together.
[0108] In some embodiments, the protective layer 3 includes 58wt% to 75wt% of the first conductive agent, 12.5wt% to 30wt% of the first binder, and 8wt% to 12.5wt% of the dispersant. Within the above range, the protective layer 3 has both good liquid absorption capacity and bonding stability, and effectively reduces the floating powder of the pole piece 10. As an example, in the protective layer 3, the content of the first conductive agent is 58wt%, 60wt%, 62wt%, 64wt%, 66wt%, 68wt%, 70wt%, 72wt%, 74wt% or 75wt%; the content of the first binder is 12.5wt%, 14wt%, 16wt%, 18wt%, 20wt%, 22wt%, 24wt%, 26wt%, 28wt% or 30wt%; the content of the dispersant is 8wt%, 9wt%, 10wt%, 11wt%, 12wt% or 12.5wt%.
[0109] In some embodiments, the specific surface area of the first conductive agent is 1 m 2 / g~1000m 2 / g. The specific surface area of the first conductive agent affects the ability of the protective layer 3 to store electrolyte. The larger the specific surface area of the first conductive agent, the stronger the ability of the protective layer 3 to store electrolyte. As an example, the specific surface area of the first conductive agent is 1m 2 / g, 10m 2 / g、100m 2 / g, 200m 2 / g、300m 2 / g, 400m 2 / g、500m 2 / g、600m 2 / g、700m 2 / g、800m 2 / g、900m 2 / g or 1000m 2 / g. It is usually related to the specific surface area of the first conductive agent and the morphology of the material. As an example, the first conductive agent includes a conductive carbon material, and the conductive carbon material includes at least one of carbon black, carbon nanotubes, carbon fibers, graphite and graphene, wherein the specific surface area of carbon black is greater than 5m 2 / g, the specific surface area of carbon nanotubes is greater than 1m 2 / g, the specific surface area of graphene is 1m 2 / g~500m 2 / g, the specific surface area of graphite is 1m 2 / g~1000m 2 / g, the specific surface area of carbon fiber is 1m 2 / g~1000m 2 / g.
[0110] In some embodiments, the D50 particle size (i.e., average particle size) of the first conductive agent is 1 nm to 50 μm. The larger the D50 particle size of the first conductive agent, the greater the porosity of the protective layer 3, so that the liquid storage space of the protective layer 3 is increased, and the electrolyte is also more likely to penetrate the protective layer 3 to reach the active material layer 2. However, if the D50 particle size of the first conductive agent is too large, it will affect the thickness of the protective layer 3, and the D50 particle size of the first conductive agent is too large, which will easily reduce the specific surface area of the first conductive agent. As an example, the D50 particle size of the first conductive agent is 1 nm, 5 nm, 10 nm, 100 nm, 200 nm, 500 nm, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm or 50 μm. As an example, the first conductive agent includes a conductive carbon material, and the conductive carbon material includes at least one of carbon black, carbon nanotubes, carbon fibers, graphite and graphene, wherein the D50 particle size of carbon black is 1nm to 200nm, the D50 particle size of carbon nanotubes is 1nm to 100nm, the D50 particle size of graphene is 1μm to 50μm, the D50 particle size of graphite is 10nm to 20μm, and the D50 particle size of carbon fiber is 5nm to 1μm.
[0111] In some embodiments, the oil absorption value of the first conductive agent is greater than or equal to 500mL / 100g. Usually, the solvent in the electrolyte is an organic solvent, and the oil absorption value of the first conductive agent will affect the ability of the protective layer 3 to absorb the electrolyte. By setting the oil absorption value of the first conductive agent to be greater than or equal to 500mL / 100g, the protective layer 3 can be quickly infiltrated with the electrolyte, thereby accelerating the electrolyte to enter the interior of the electrode 10. As an example, the oil absorption value of the first conductive agent is 500mL / 100g, 1000mL / 100g, 1500mL / 100g, 2000mL / 100g or 2500mL / 100g. As an example, the first conductive agent includes conductive carbon black, and the oil absorption value of the conductive carbon black is 1000mL / 100g; or the first conductive agent includes carbon nanotubes, and the oil absorption value of the carbon nanotubes is 500mL / 100g; or the first conductive agent includes graphene, and the oil absorption value of the graphene is 2000mL / 100g; or the first conductive agent includes graphite, and the oil absorption value of the graphite is 500mL / 100g.
[0112] In some embodiments, the conductivity of the first conductive agent is 3000S·cm to 12000S·cm. The greater the conductivity of the first conductive agent, the greater the conductivity of the protective layer 3, which is beneficial to reduce the internal resistance of the battery 100. As an example, the conductivity of the first conductive agent is 3000S·cm, 5000S·cm, 7000S·cm, 9000S·cm, 10000S·cm or 12000S·cm. As an example, the first conductive agent includes carbon black, and the conductivity of carbon black is 3000S·cm; or the first conductive agent includes carbon nanotubes, and the conductivity of carbon nanotubes is 5000S·cm; or the first conductive agent includes graphene, and the conductivity of graphene is 12000S·cm; or the first conductive agent includes graphite, and the conductivity of graphite is 5000S·cm; or the first conductive agent includes carbon fiber, and the conductivity of carbon fiber is 5000S·cm.
[0113] In some embodiments, the porosity of the protective layer 3 is 5% to 99%. The greater the porosity of the protective layer 3, the greater the liquid storage capacity of the protective layer 3, and the better the liquid absorption capacity of the protective layer 3. As an example, the porosity of the protective layer 3 is 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or 99%.
[0114] In some embodiments, the thickness of the protective layer 3 is 0.2 μm to 50 μm. Generally, the thicker the protective layer 3 is, the better the covering effect of the protective layer 3 on the floating powder is. However, the increase in the thickness of the protective layer 3 will increase the resistance of the electrolyte to the electrode 10, and the rate performance of the battery 100 will decrease. As an example, the thickness of the protective layer 3 is 0.2 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm. Here, the thickness of the protective layer 3 is an average thickness.
[0115] In some embodiments, the thickness of the protective layer 3 is 0.2 μm to 10 μm. When the thickness of the protective layer 3 is within this range, the battery 100 has both good rate performance and a covering effect on floating powder. As an example, the thickness of the protective layer 3 is 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm. Here, the thickness of the protective layer 3 is an average thickness.
[0116] In some embodiments, the pole piece 10 is a thick pole piece, wherein the thickness of the active material layer 2 is greater than 30 μm. By increasing the thickness of the active material layer 2, the content of the active material in the pole piece 10 is increased, thereby increasing the energy density of the battery 100. As an example, the thickness of the active material layer 2 is 31 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm or 150 μm.
[0117] In some embodiments, the pole piece 10 is a thick pole piece, and the thickness of the pole piece 10 is greater than 60 μm. As an example, the thickness of the pole piece 10 is 61 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 170 μm, 190 μm, 20 μm, 250 μm, 280 μm or 300 μm.
[0118] In some embodiments, see Figure 7 , the laser etched concave portion 22 includes a long strip-shaped groove, the groove extends along the first direction of the active material layer 2, and the length H1 of the groove extending in the first direction is less than or equal to the length H2 of the active material layer 2 in the first direction. For example, the first direction can be the transverse direction (TD direction) or the longitudinal direction (MD direction) of the active material layer 2. As an example, the first direction is the X direction, the groove extends along the X direction on the active material layer 2, and the length H1 of the groove is equal to the length H2 of the active material layer 2. As an example, the first direction is the X direction, the groove extends along the X direction on the active material layer 2, and the length H1 of the groove is less than the length H2 of the active material layer 2. In other cases, the first direction may also be the Y direction.
[0119] In some embodiments, the number of laser-etched recesses 22 is multiple, and the multiple laser-etched recesses 22 are spaced apart. By increasing the number of laser-etched recesses 22 provided on the active material layer 2, and distributing the multiple laser-etched recesses 22 at intervals, that is, the multiple laser-etched recesses 22 are dispersed on the active material layer 2, it is beneficial to improve the uniformity and rate of electrolyte infiltration into the active material layer 2, and reduce the concentration polarization inside the pole piece 10. Optionally, the spacing between two adjacent laser-etched recesses 22 is 0.01 mm to 100 mm. The spacing between two adjacent laser-etched recesses 22 should not be too large, otherwise the number of laser-etched recesses 22 that can be provided per unit area will be reduced. As an example, it is 0.01 mm, 0.1 mm, 1 mm, 10 mm, 20 mm, 30 mm, 40 mm, 50 mm, 60 mm, 70 mm, 80 mm, 90 mm or 100 mm. As an example, see Figure 7The spacing between two adjacent laser-etched recesses 22 may refer to a spacing W1 between two adjacent laser-etched recesses 22 in the transverse direction of the active material layer 2 , or may refer to a spacing W2 between two adjacent laser-etched recesses 22 in the longitudinal direction of the active material layer 2 .
[0120] In some embodiments, see Figure 6 , the width of the laser-etched concave portion 22 remains unchanged or becomes smaller along the direction close to the current collector 1. In this way, the width of the laser-etched concave portion 22 is the largest at the opening, which is not only conducive to the production of the laser-etched concave portion 22 itself, but also conducive to making the protective layer 3 extend into the laser-etched concave portion 22 and combine with the inner surface of the laser-etched concave portion 22 when producing the protective layer 3.
[0121] In some embodiments, see Figure 6 The sidewall of the laser-etched concave portion 22 may be a straight wall or a curved wall. As an example, the sidewall of the laser-etched concave portion 22 is an arc-shaped curved wall. When the sidewall of the laser-etched concave portion 22 is a straight wall, the sidewall of the laser-etched concave portion 22 may extend along the thickness direction of the active material layer 2, or may be inclined relative to the thickness direction of the active material layer 2.
[0122] In some embodiments, see Figure 6 The laser-etched concave portion 22 is cut along the thickness direction of the active material layer 2 , and the cross section of the laser-etched concave portion 22 is V-shaped, trapezoidal, square, semicircular or semi-elliptical.
[0123] In some embodiments, the average width of the laser-etched concave portion 22 is 1 μm to 300 μm. The width of the laser-etched concave portion 22 should not be too small, otherwise it is not conducive to the protective layer 3 extending into the laser-etched concave portion 22, but it should not be too large, otherwise the laser-etched concave portion 22 will be too wide, resulting in an insufficient mass proportion of the active material layer 2 in the pole piece 10. As an example, the average width of the laser-etched concave portion 22 is 1 μm, 5 μm, 10 μm, 50 μm, 100 μm, 150 μm, 200 μm, 250 μm or 300 μm.
[0124] In some embodiments, the depth of the laser-etched recess 22 is less than the thickness of the active material layer 2. Generally, the closer the active material layer 2 in the pole piece 10 is to the current collector 1, the farther it is from the electrolyte, and the less likely it is to be infiltrated by the electrolyte, resulting in a more likely concentration polarization inside the pole piece 10. The deeper the depth of the laser-etched recess 22, the closer it is to the current collector 1, so that the electrolyte is more likely to quickly penetrate into the part of the active material layer 2 close to the current collector 1 through the laser-etched recess 22, reducing the concentration polarization inside 10. Optionally, the depth of the laser-etched recess 22 is greater than half the thickness of the active material layer 2. As an example, the ratio of the depth of the laser-etched recess 22 to the thickness of the active material layer 2 is 0.5, 0.6, 0.7, 0.8, 0.9, 0.95 or 0.98.
[0125] In some embodiments, the active material layer 2 includes a second conductive agent, and the content of the second conductive agent in the active material layer 2 increases along the direction close to the current collector 1. In the active material layer 2, the second conductive agent has a better wetting effect on the electrolyte than the first active material. By increasing the content of the second conductive agent in the part of the active material layer 2 close to the current collector 1, it is beneficial to promote the rapid migration of lithium ions into the interior of the active material layer 2, improve the uniformity of the active material layer 2 infiltrating the electrolyte, and reduce the concentration polarization inside the active material layer 2. As an example, see Figure 5 The active material layer 2 includes a plurality of stacked sub-active material layers, and the content of the second conductive agent in each sub-active material layer gradually increases along a direction approaching the current collector 1 .
[0126] In some embodiments, the active material layer 2 includes a first active material, which is in a granular form. In the active material layer 2, the average particle size of the first active material increases along the direction close to the current collector 1. By increasing the average particle size of the first active material in the portion of the active material layer 2 close to the current collector 1, the porosity of the portion of the active material layer 2 close to the current collector 1 can be increased, which is conducive to promoting the migration of lithium ions into the interior of the active material layer 2 through the pores, improving the uniformity of the electrolyte infiltration of the active material layer 2, and reducing the concentration polarization inside the active material layer 2. As an example, see Figure 5 The active material layer 2 includes a plurality of stacked sub-active material layers, and the average particle size of the first active material in each sub-active material layer gradually increases along the direction approaching the current collector 1 .
[0127] Second, see Figure 8 The present application also provides a method for preparing a pole piece 10, comprising:
[0128] S01, disposing an active material layer 2 on the current collector 1, wherein the active material layer 2 has a first surface 21 facing away from the current collector 1;
[0129] S02, performing laser etching on the active material layer 2 to generate a laser-etched concave portion 22 extending from the first surface 21 to the inside of the active material layer 2;
[0130] S03, providing a first slurry, wherein the first slurry includes a first binder and a first solvent;
[0131] S04, performing film forming treatment on the first slurry on the first surface 21 and in the laser-etched concave portion 22 to obtain a first wet film layer 3a;
[0132] S05 , drying the first wet film layer 3 a to volatilize the first solvent, thereby obtaining the protective layer 3 .
[0133] In the embodiment of the present application, since laser etching is used to prepare the laser etched recess 22, there will be floating powder (i.e., residual dust at the micron level) on the surface of the active material layer 2. By setting a first wet film layer 3a on the first surface 21 of the active material layer 2 and in the laser etched recess 22, the first wet film layer 3a includes a first slurry, and the first slurry includes a first solvent and a first binder. The first slurry has a certain fluidity as a wet material; in this way, the first wet film layer 3a will not only cover the floating powder on the surface of the active material layer 2, but also a small amount of the first slurry in the first wet film layer 3a will penetrate into the active material layer 2. After that, the first slurry loses the first solvent after drying and solidifies to form a protective layer 3. The floating powder on the surface of the active material layer 2 will also be solidified in the interface area where the protective layer 3 and the active material layer 2 are combined, thereby reducing the dust from escaping from the electrode 10 and entering the electrolyte, reducing the risk of dust adhesion to the diaphragm, and thereby reducing the risk of short and self-discharge in the battery 100.
[0134] In some embodiments, see Figure 8 Middle (a) Figure, Figure 8 (b) Figure and Figure 8 In Figure (c), step S01 specifically includes:
[0135] S011, providing a second slurry, wherein the second slurry includes a first active material, a second binder, and a second solvent;
[0136] S012, performing film-forming treatment on the current collector 1 with the second slurry to obtain a second wet film layer 2a;
[0137] S013 , drying the second wet film layer 2 a to volatilize the second solvent, thereby obtaining the active material layer 2 .
[0138] In short, the process of preparing the active material layer 2 on the current collector 1 includes: subjecting the second slurry to a film-forming treatment on the current collector 1 to obtain a second wet film layer 2a, and drying the second wet film layer 2a to obtain the active material layer 2. The film-forming treatment method here includes but is not limited to at least one of gravure coating, micro-gravure coating, spraying and electrostatic spinning technology. The first active material and the second binder can refer to the description of the first aspect. The second solvent can be selected according to the type of pole piece 10 prepared. As an example, when the pole piece 10 is a positive pole piece, the second solvent includes N-methylpyrrolidone (NMP), and when the pole piece 10 is a negative pole piece, the second solvent includes water. Optionally, the second slurry also includes a second conductive agent, and the second conductive agent can refer to the description of the first aspect. In addition, the drying treatment of the second wet film layer 2a may specifically include: drying the second wet film layer 2a in an oven, when the pole piece 10 is a positive pole piece, the drying temperature may be 40°C to 150°C; when the pole piece 10 is a negative pole piece, the drying temperature may be 20°C to 110°C.
[0139] In some embodiments, see Figure 8 In the middle (d) figure, the process of preparing the laser-etched concave portion 22 on the active material layer 2 includes: using a laser beam to locally irradiate the active material layer 2 from the first surface 21 of the active material layer 2, so that the material (including the first active material, the second conductive agent, the second binder, etc.) in the irradiated area on the active material layer 2 is vaporized and evaporated, so that the area irradiated by the laser beam on the active material layer 2 is thinned in the thickness direction to form a pit, that is, the laser-etched concave portion 22. As an example, a laser engraving machine can be used to emit a laser beam, and the power of the laser etching during the laser etching process can be adjusted according to the type of etched material, the size of the laser-etched concave portion 22 to be formed, etc.
[0140] In some embodiments, see Figure 8 Figure (e) and Figure 8 In the middle (f) figure, the process of preparing the protective layer 3 on the active material layer 2 includes: forming a film of the first slurry on the first surface 21 of the active material layer 2 and in the laser-etched concave portion 22 to obtain a first wet film layer 3a, and drying the first wet film layer 3a to obtain the protective layer 3. Similarly, the film forming method here includes but is not limited to at least one of gravure coating, micro-gravure coating, spraying and electrospinning technology. Optionally, the first solvent includes at least one of water, N-methylpyrrolidone, ethylene glycol and isopropanol. Optionally, the first binder includes at least one of carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE) and styrene-butadiene rubber (SBR).
[0141] In some embodiments, the first slurry further includes a first conductive agent and / or a second active material. As an example, the first slurry further includes a first conductive agent, or the first slurry further includes a second active material, or the first slurry further includes a second active material and a first conductive agent. Optionally, the first conductive agent includes at least one of a conductive carbon material and a conductive ceramic. Optionally, the conductive carbon material includes at least one of carbon black, carbon nanotubes, carbon fibers, acetylene black, graphite, and graphene. Optionally, carbon black includes at least one of conductive carbon black Super P, superconducting carbon black, and Ketjen black. Optionally, carbon nanotubes include at least one of single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs).
[0142] In some embodiments, the content of the first solvent in the first slurry is 10wt% to 97wt%. The content of the first solvent in the first slurry will affect the molding effect of the first wet film layer 3a, and then affect the protective layer 3. In the first slurry, if the content of the first solvent is too high, the first slurry will be easy to drip, and the first wet film layer 3a will be difficult to form, while if the content of the first solvent is too low, the first slurry will have insufficient fluidity, and the uniformity and continuity of the first wet film layer 3a will be affected. As an example, the content of the first solvent in the first slurry is 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, 90wt%, 95wt% or 97wt%.
[0143] In some embodiments, the solid content in the first slurry is 3wt% to 90wt%. The solid content in the first slurry refers to the total content of other substances except the first solvent. If the solid content in the first slurry is too high, the fluidity of the first slurry is insufficient, and if the solid content in the first slurry is too low, the first slurry is easy to drip. As an example, the solid content in the first slurry is 3wt%, 5wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt% or 90wt%.
[0144] In some embodiments, the viscosity of the first slurry is 10cp to 15000cp. The viscosity of the first slurry affects the thickness of the protective layer 3. The smaller the viscosity of the first slurry, the thinner the protective layer 3 is. The larger the viscosity of the first slurry, the thicker the protective layer 3 is. As an example, the viscosity of the first slurry is 10cp, 100cp, 500cp, 1000cp, 2000cp, 3000cp, 5000cp, 8000cp, 10000cp, 12000cp or 15000cp.
[0145] In some embodiments, the first slurry further includes a dispersant and a first conductive agent. The dispersant is beneficial to improving the dispersion effect of the first conductive agent in the first solvent. Optionally, the dispersant includes at least one of anhydride, polyvinyl pyrrolidone (PVP), sulfate, sulfonate, poly (N-vinyl acetamide) (PNVA), polyvinyl alcohol (PVA) and polyethylene glycol.
[0146] In some embodiments, based on the total mass of the first conductive agent, the first binder and the dispersant, the contents of the first conductive agent, the first binder and the dispersant are as follows: 1 wt% to 60 wt% of the first conductive agent, 10 wt% to 99 wt% of the first binder and 0 wt% to 30 wt% of the dispersant. As an example, the content of the first conductive agent is 1 wt%, 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt% or 60 wt%; the content of the first binder is 10 wt%, 20 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt%, 70 wt%, 80 wt%, 90 wt% or 99 wt%; the content of the dispersant is 0 wt%, 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt% or 30 wt%.
[0147] In some embodiments, the first slurry can be prepared by wet pulping. Specifically, the first solvent, the dispersant, and the first binder are prepared into a glue solution in a mixing device, and then the first conductive agent is added and mixed to prepare the first slurry. The mixing device here includes but is not limited to a stirrer, a ball mill, a high-speed disperser, a grinder, etc. Of course, in some embodiments, the first solvent and the first binder can also be prepared into a glue solution in a mixing device, and then the first conductive agent and the dispersant are added and mixed to prepare the first slurry.
[0148] In some embodiments, the first slurry may be prepared by dry mixing. Specifically, the first conductive agent, the first binder and the dispersant are first mixed evenly in a mixing device, and then the first solvent is added for mixing to prepare the first slurry. Of course, in some embodiments, the first binder and the first solvent may be prepared into a binder glue, and the first conductive agent and the dispersant are mixed evenly in a mixing device, and then the binder glue is added for mixing to prepare the first slurry.
[0149] In some embodiments, the first slurry includes a first solvent, a dispersant, a first conductive agent, and a first binder. Figure 8 Figure (e) and Figure 8In Figure (f), the drying treatment of the first wet film layer 3a may specifically include: drying the first wet film layer 3a in an oven, and the drying temperature may be 20°C to 130°C. As an example, the drying temperature is 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C or 130°C.
[0150] In some embodiments, the first slurry includes a first solvent, a second active material, a dispersant, a first conductive agent, and a first binder. For the second active material, see the description of the first aspect. Figure 8 Figure (e) and Figure 8 In Figure (f), the drying treatment of the first wet film layer 3a may specifically include: drying the first wet film layer 3a in an oven. When the electrode 10 is a positive electrode, the drying temperature may be 40°C to 150°C; when the electrode 10 is a negative electrode, the drying temperature may be 20°C to 110°C.
[0151] Third, see Fig. 9 The embodiment of the present application further provides a battery 100 , which includes the above-mentioned electrode 10 .
[0152] The following is a description with reference to specific embodiments.
[0153] Example 1
[0154] S1. Preparation of electrode slurry (dry mixing): First, 12g of binder CMC was mixed with 738g of water to prepare glue solution, 960g of active material graphite and 13g of conductive agent conductive carbon black Super P (SP for short) were taken, the above materials were ground and mixed, 262.5g of glue solution and 234g of water were added for kneading, and then 487.5g of glue solution and 203.3g of water were added for stirring, and finally 37.5g of SBR was added to obtain an electrode slurry with a solid content of 45.5wt%. The current collector is copper foil, and the thickness of the current collector is 6um.
[0155] S2. Preparation of active material layer: coating the electrode slurry on the current collector by slot-die coating, drying the electrode sheet in an oven, curing the electrode slurry to form an active material layer, and performing roller pressing;
[0156] S3, etching grooves: etching grooves on the active material layer by laser etching, the power of the laser etching is 10W;
[0157] S4. Prepare conductive slurry: grind and mix 58g conductive carbon black, 30g CMC+SBR in total, and 12g PVP, then add into 85g water to prepare conductive slurry with a viscosity of 71cp.
[0158] S5. Prepare a conductive layer: apply a conductive slurry on the active material layer obtained in step S3 by gravure coating, dry the electrode after passing through an oven, and solidify the conductive slurry to form a conductive layer.
[0159] Example 2
[0160] The only difference from Example 1 is S4: Preparation of conductive slurry: 62 g of conductive carbon black, 28 g of CMC+SBR in total, and 10 g of PVP were ground and mixed, and then added into 83 g of water to prepare a conductive slurry with a viscosity of 76 cp.
[0161] Example 3
[0162] The only difference from Example 1 is S4: Preparation of conductive slurry: 66 g of conductive carbon black, 26 g of CMC+SBR in total, and 8 g of PVP were ground and mixed, and then added into 80 g of water to prepare a conductive slurry with a viscosity of 74 cp.
[0163] Example 4
[0164] The only difference from Example 2 is that the amount of water used in S4 is 87 g of water, and the viscosity of the prepared conductive paste is 63 cp.
[0165] Example 5
[0166] The only difference from Example 2 is that the amount of water used in S4 is 82 g of water, and the viscosity of the prepared conductive paste is 75 cp.
[0167] Example 6
[0168] The only difference from Example 2 is that the amount of water used in S4 is 76 g of water, and the viscosity of the prepared conductive paste is 89 cp.
[0169] Example 7
[0170] The only difference from Example 1 is S4: preparing a conductive paste: grinding and mixing 30 g of conductive carbon black, 5 g of PAA and 5 g of PVP, and adding them into 88 g of water to prepare a conductive paste with a viscosity of 25 cp.
[0171] Example 8
[0172] The only difference from Example 7 is that the amount of water used in S4 is 75 g of water, and the viscosity of the prepared conductive paste is 120 cp.
[0173] Example 9
[0174] The only difference from Example 8 is that the conductive carbon black is replaced by acetylene black in S4.
[0175] Comparative Example 1
[0176] The only difference from Embodiment 1 is that there are no steps S4 and S5.
[0177] The formula of the conductive paste in the above embodiments is shown in Table 1.
[0178] Table 1
[0179]
[0180]
[0181] The pole piece samples provided in Examples 1 to 9 and Comparative Example 1 were characterized as follows:
[0182] 1. Measure the thickness of the conductive layer in the electrode samples provided in Examples 1 to 8 and Comparative Example 1: The thickness of the sample before and after the conductive layer is coated is measured by a micrometer, and the difference is taken to obtain the thickness of the conductive layer. The results are recorded in Table 2. From the results in Table 2, it can be seen that when the viscosity of the conductive paste is similar (Examples 1 to 3 and Example 5), the thickness of the obtained conductive layer is similar, and as the solid content and viscosity of the conductive paste increase (Example 4, Example 2, Example 5 and Example 6), the thickness of the conductive layer increases.
[0183] Table 2
[0184] Group Conductive layer thickness / μm Example 1 1.45 Example 2 1.45 Example 3 1.45 Example 4 0.85 Example 5 1.50 Example 6 2.60 Example 7 0.6 Example 8 3.15 Comparative Example 1 0
[0185] 2. Morphology characterization: Use argon ion precision cross-section cutting to cut the electrode cross section. After obtaining a flat cross section, use a scanning electron microscope (SEM) to observe the cross-sectional morphology and measure the thickness of the conductive layer.
[0186] like Fig.10 and Fig.11 Shown are SEM images of the electrode provided in Example 8 at different magnifications. It can be seen from the figure that the conductive layer covers the surface of the active material layer and fills the grooves on the active material layer. The average thickness of the portion of the conductive layer covering the surface of the active material layer is 2.91 μm, and the thickness of the portion of the conductive layer filling the grooves is 6.85 μm.
[0187] like Fig.12 and Fig.13 Shown are SEM images of the electrode provided in Example 1 at different magnifications. It can be seen from the figure that the conductive layer also covers the surface of the active material layer and fills the grooves on the active material layer. The average thickness of the portion of the conductive layer covering the surface of the active material layer is 1.275 μm, and the thickness of the portion of the conductive layer filling the grooves is 2.85 μm.
[0188] like Fig.14Shown is a SEM image of the electrode provided in Comparative Example 1. The area circled in the figure is the area where the active material layer is etched. It can be seen from the figure that the particles in the etched area on the surface of the electrode are relatively loose. This is because when the high-energy laser etches the active material layer, the binder is carbonized, and the active material and conductive agent in the active material layer become loose and form micron-sized dust.
[0189] 3. Use a contact angle meter to test the diffusion time of 1 mol / L LiPF6 electrolyte (solvent volume ratio EC:DMC:EMC=1:1:1) on the electrode, and use a high-speed camera to record the process pictures. Specifically, the electrodes provided in Example 8 and Comparative Example 1 were tested respectively, and three different positions were selected for each electrode for testing. The time from the beginning of the dripping of the electrolyte to the surface of the electrode to the time when the electrolyte on the surface of the electrode is completely absorbed by the electrode (the contact angle no longer changes) was recorded, and the average value of the time obtained by the three tests was calculated as the diffusion time of the electrolyte on the electrode, and the results are recorded in Table 3. It can be seen from the data in Table 3 that the diffusion time of the electrolyte on the active material layer is 28.583s, and the diffusion time on the conductive layer is 12.173s, indicating that the conductive layer can better infiltrate the electrolyte, and the conductive layer can accelerate the penetration rate of the electrolyte in the electrode and reduce the concentration polarization inside the electrode.
[0190] Table 3
[0191]
[0192] 4. Pole surface cleanliness test:
[0193] 4.1. For Example 8, at different stages of the electrode preparation, the cleanliness of the sample surface at different stages was investigated. The specific method was: Wear clean latex gloves to wipe the electrode surface, and observe the dirtiness of the position where the latex gloves contacted the electrode. The results are as follows: Fig.15 As shown. Among them, Fig.15 Figure (a) is a surface cleanliness test photo of the sample provided in step S2 (i.e., the sample before etching the active material layer). It can be seen from the photo that there is no obvious stain at the position of the latex glove contacting the active material layer, indicating that there is very little floating powder on the active material layer before etching; Fig.15 Figure (b) is a surface cleanliness test photo of the sample provided in step S3 (i.e., the sample after the active material layer is etched). From the photo, it can be seen that there are obvious black stains at the position where the latex gloves contact the active material layer, indicating that after etching, the active material layer has serious floating powder; Fig.15 Figure (c) is a surface cleanliness test photograph of the sample provided in step S5 (i.e., the sample after the active material layer is covered with a conductive layer). From the photograph, it can be seen that there are no obvious stains at the position where the latex gloves contact the conductive layer, indicating that after the active material layer is covered with a conductive layer, the floating powder on the surface of the electrode is reduced.
[0194] 4.2. The pole pieces provided in Example 8 and Comparative Example 1 were respectively wound with the diaphragm and then separated, and the cleanliness of the diaphragm surface was observed. The results are as follows: Fig.16 As shown. Fig.16 It can be seen that the surface of the diaphragm wound around the electrode piece provided in Comparative Example 1 has obvious black dirt, while the surface of the diaphragm wound around the electrode piece provided in Example 8 is relatively clean, indicating that the active material layer has serious powder floating after laser etching, and after the active material layer after laser etching is covered with a conductive layer, the powder floating is significantly reduced.
[0195] 5. Rate performance test:
[0196] 5.1. Preparation of batteries: Batteries were prepared using the electrodes provided in Example 8 and Comparative Example 1 as negative electrodes (referred to as battery No. 1 and battery No. 2 for easy distinction), the positive electrode, separator and electrolyte of each battery were the same, wherein the active material layer of the positive electrode included lithium cobalt oxide (97.6wt%), PVDF (1.3wt%) and SP (1.1wt%), the separator was a polyethylene film, and the electrolyte was 1 mol / L LiPF6 electrolyte (solvent volume ratio EC:DMC:EMC=1:1:1).
[0197] 5.2. The prepared batteries were tested for rate performance according to the following test methods:
[0198] (1) Leave for 3 minutes;
[0199] (2) Constant current and constant voltage charging: charge at 0.2C to 4.47V, and cut off at 0.02C;
[0200] (3) Leave for 5 minutes;
[0201] (4) Constant current discharge: discharge to 2.75V at different test rates; the test rates are 0.2C, 0.5C, 1C, 1.5C, and 2C;
[0202] (5) Leave for 5 minutes;
[0203] (6) End, the test results show the battery capacity;
[0204] (7) The battery capacities obtained at different test rates were compared with the battery capacities at a test rate of 0.2C to obtain the capacity retention rates at different test rates. The results are recorded in Table 4.
[0205] Table 4
[0206] Group 0.2C discharge 0.5C discharge 1C discharge 1.5C discharge 2C discharge Example 8 100% 97.6% 95.5% 92.4% 74.5% Comparative Example 1 100% 97.7% 94.2% 82.9% 63.2%
[0207] It can be seen from the results in Table 4 that at low rates (0.2C, 0.5C), the capacity retention rates of battery No. 1 prepared using the electrode sheet provided in Example 8 and battery No. 2 prepared using the electrode sheet provided in Comparative Example 1 are close, and as the rate increases, the capacity retention rate of battery No. 1 is higher than that of battery No. 2, especially at high rates (1.5C, 2C), the capacity retention rate of battery No. 1 is significantly higher than that of battery No. 2, indicating that the provision of a conductive layer can significantly improve the rate performance of the battery.
[0208] 6. K value test:
[0209] 6.1. Preparation of batteries: Batteries were prepared using the pole pieces provided in Example 8, Example 9 and Comparative Example 1 as negative electrodes, respectively. The positive electrode, separator and electrolyte of each battery were the same, wherein the active material layer of the positive electrode included lithium cobalt oxide (97.6wt%), PVDF (1.3wt%) and SP (1.1wt%), the separator was a polyethylene film, and the electrolyte was 1 mol / L LiPF6 electrolyte (solvent volume ratio EC:DMC:EMC=1:1:1).
[0210] 6.2. The prepared batteries were tested for K value according to the following test method: after the capacity was separated and the battery was left standing at room temperature for 96±4h, the OCV1 was tested to obtain the voltage U1, and then after the battery was left standing at room temperature for 48±4h (interval time t), the OCV2 was tested to obtain the voltage U2, and the K value was obtained by calculating (U1-U2) / t. The test results are recorded in Table 5.
[0211] Table 5
[0212] Group K Value Example 8 0.0422mV / h Example 9 0.0225mV / h Comparative Example 1 0.0925mV / h
[0213] The K value of a battery refers to the voltage drop per unit time, usually expressed in mV / h, and is an indicator used to measure the self-discharge rate of a lithium battery.
[0214] It can be seen from the results in Table 5 that compared with Comparative Example 1, the K values of Examples 8 and 9 are significantly reduced, which indicates that a conductive layer (i.e., a protective layer) is added to the electrode after laser etching. The conductive layer can cover the floating powder and reduce the risk of the floating powder entering the electrolyte and the diaphragm, thereby significantly reducing the K value of the battery (here, the battery cell).
[0215] The embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method and core idea of the present application. At the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A pole piece, characterized in that: include: current collector; an active material layer, located on the current collector, the active material layer having a first surface facing away from the current collector, and a laser-etched concave portion extending from the first surface to the interior of the active material layer; A protective layer covers the first surface and the inner surface of the laser-etched concave portion, and the protective layer includes a first adhesive.
2. The pole piece according to claim 1, characterized in that: The protective layer adapts to the laser-etched recess and defines a receiving groove, wherein the notch of the receiving groove is located at a side of the protective layer away from the active material layer.
3. The pole piece according to claim 2, characterized in that: The protective layer also includes a second active material.
4. The pole piece according to any one of claims 1 to 3, characterized in that: The protection layer further includes a first conductive agent.
5. The pole piece according to claim 4, characterized in that: The ability of the protective layer to absorb the electrolyte is better than the ability of the active material layer to absorb the electrolyte.
6. The pole piece according to claim 5, characterized in that: The porosity of the protective layer is greater than the porosity of the active material layer.
7. The pole piece according to claim 5, characterized in that: The active material layer includes a first active material, and the first conductive agent has an oil absorption value greater than an oil absorption value of the first active material.
8. The pole piece according to claim 5, characterized in that: The active material layer further includes a second conductive agent, and a mass content of the first conductive agent in the protective layer is greater than a mass content of the second conductive agent in the active material layer.
9. The pole piece according to claim 5, characterized in that: The active material layer includes a first active material, the content of the first active material in the active material layer is greater than 50wt%, and the total mass percentage of the first conductive agent in the protective layer is greater than 50wt%.
10. The pole piece according to claim 5, characterized in that: The protective layer includes 1 wt % to 80 wt % of the first conductive agent, 10 wt % to 99 wt % of the first binder, and the protective layer further includes 0 wt % to 30 wt % of a dispersant.
11. The pole piece according to claim 10, characterized in that: The protective layer includes 58 wt % to 75 wt % of the first conductive agent, 12.5 wt % to 30 wt % of the first binder, and 8 wt % to 12.5 wt % of the dispersant.
12. The pole piece according to claim 11, characterized in that: The dispersant includes at least one of anhydride, polyvinyl pyrrolidone, sulfate, poly(N-vinylacetamide), polyvinyl alcohol, sulfonate and polyethylene glycol; or, the dispersant includes at least one of ionic dispersant, non-ionic dispersant and polymer dispersant.
13. The pole piece according to claim 4, characterized in that: The first conductive agent includes at least one of a conductive carbon material and a conductive ceramic.
14. The pole piece according to claim 13, characterized in that: The conductive carbon material includes at least one of carbon black, carbon nanotubes, carbon fibers, acetylene black, graphite and graphene.
15. The pole piece according to claim 4, characterized in that: The specific surface area of the first conductive agent is 1 m 2 / g~1000m 2 / g; and / or, the D50 particle size of the first conductive agent is 1nm~50μm; and / or, the oil absorption value of the first conductive agent is greater than or equal to 500mL / 100g; and / or, the conductivity of the first conductive agent is 3000S·cm~12000S·cm.
16. The pole piece according to claim 1, characterized in that: The first binder includes at least one of carboxymethyl cellulose, polyacrylic acid, polyvinylidene fluoride, polytetrafluoroethylene and styrene-butadiene rubber.
17. The pole piece according to claim 1, characterized in that: The laser-etched recess includes at least one of a groove and a through hole.
18. The pole piece according to claim 1, characterized in that: The laser-etched concave portion includes a long strip-shaped groove extending along a first direction of the active material layer, and a length of the groove extending in the first direction is less than or equal to a length of the active material layer in the first direction.
19. The pole piece according to claim 1, characterized in that: Along the direction approaching the current collector, the width of the laser-etched recess remains unchanged or becomes smaller.
20. The pole piece according to claim 19, characterized in that: The sidewall of the laser-etched concave portion is a straight wall or a curved wall, or, when cut along the thickness direction of the active material layer, the cross section of the laser-etched concave portion is V-shaped, trapezoidal, square, semicircular or elliptical.
21. The pole piece according to claim 1, characterized in that: The number of the laser-etched recesses is multiple, the multiple laser-etched recesses are distributed at intervals, and the distance between two adjacent laser-etched recesses is 0.01mm to 100mm; and / or the depth of the laser-etched recess is less than or equal to the thickness of the active material layer; and / or the average width of the laser-etched recess is 1μm to 300μm.
22. The pole piece according to claim 1, characterized in that: The thickness of the protective layer is 0.2 μm to 50 μm; or, the thickness of the protective layer is 0.2 μm to 10 μm; or, the porosity of the protective layer is 5% to 99%.
23. The pole piece according to claim 1, characterized in that: The thickness of the active material layer is greater than 30 μm; or the thickness of the pole piece is greater than 60 μm.
24. A method for preparing a pole piece, characterized in that: include: Disposing an active material layer on the current collector, the active material layer having a first surface facing away from the current collector; Laser etching the active material layer to generate a laser-etched recess extending from the first surface into the active material layer; Providing a first slurry, wherein the first slurry includes a first binder and a first solvent; Performing a film-forming process on the first surface and the laser-etched concave portion with the first slurry to obtain a first wet film layer; The first wet film layer is dried to evaporate the first solvent, thereby obtaining a protective layer.
25. The method for preparing a pole piece according to claim 24, characterized in that: The first slurry also includes a first conductive agent and / or a second active material; and / or, the content of the first solvent in the first slurry is 10wt% to 97wt%; and / or, the solid content in the first slurry is 3wt% to 90wt%; and / or, the viscosity of the first slurry is 10cp to 15000cp; and / or, the first solvent includes at least one of water, N-methylpyrrolidone, ethylene glycol and isopropanol.
26. The method for preparing a pole piece according to claim 24, characterized in that: The step of providing an active material layer on the current collector comprises: providing a second slurry, the second slurry comprising a first active material, a second binder, and a second solvent; Performing a film-forming process on the second slurry on the current collector to obtain a second wet film layer; The second wet film layer is dried to evaporate the second solvent, thereby obtaining an active material layer.
27. A battery, characterized in that: A pole piece comprising the pole piece according to any one of claims 1 to 23 or a pole piece prepared by the method for preparing the pole piece according to any one of claims 24 to 26.
Citation Information
Cited By
Electrode sheet and preparation method therefor, and battery
WO2026076878A1